THE RELATIONSHIP BETWEEN DIET PATTERNS AND HYPERTENSION EVENTS IN POLARA PUBLIC HEALTH CENTER IN KONAWE ISLANDS DISTRICT: DIET PATTERNS AND HYPERTENSION - La Djabo Buton; Fitri Fadmi (STIKes Mandala Waluya Kendari, 2022)
Background: Hypertension is a non-communicable disease that is still a health problem in the work area of the Polara Health Center since 2018 until now in 2020. Hypertension has increased in cases in the last three years. In 2018 8 146 cases of hypertension then increased to 154 cases in 2019 and decreased in 2020. The results of the initial survey showed that 70% of hypertensive patients had unhealthy eating patterns such as consuming fast food containing preservatives, too high salt content in food, excess fat consumption. This study aims to determine the relationship between diet and the incidence of hypertension in the Polara Health Center Work Area ,Konawe Islands Regency. Methods: This research uses analytical research method with Cross Sectional Study approach. The population in this study were all outpatients seeking treatment at the Polara Public Health Center for the period January to February 2021 totaling 268 people, with a total sample of 73 people selected by simple random sampling technique. Results: The results showed that 43.8% of respondents who have a poor diet and have hypertension ,9.6% who do not have hypertension. Then there are 13.7% of respondents who have a good diet but have hypertension ,32.9% who do not have hypertension. The results of statistical tests using the chi square test obtained a p-value of 0.000 and a coefficient of Phi (φ) = 0.531, so the null hypothesis was rejected, meaning that there was a moderate relationship between diet and the incidence of hypertension at Polara Health Center, Konawe Islands Regency. Conclusions: diet has significant impact to hypertension at Polara Health Center, Konawe Islands Regency.